PENGEMBANGAN INDIKATOR EVALUASI PROSES PERKULIAHAN DI PERGURUAN TINGGI - Rusilowati, Ani (Universitas Negeri Semarang, 2008)
The lecturing process is the ones of the education aspects to be evaluate, behind input and output aspects, at the university. The lecturing process must be planning, implementing, and evaluating. Evaluator of the lecturing process usually to be done by lectures. Evaluation subject are university students. Lectures rarely to evaluate their performs and competencies. In order to increase the university quality, the perform and competencies lectures, activity, interest, and motivation students were evaluated. Evaluation of the perform and competencies lectures by students is a university policy. Kata kunci: indikator, evaluasi, proses perkuliahan